Tegoribatidae of North America, with proposal of Protectoribates gen. nov., and new species (Acari, Oribatida, Tegoribatidae) - Behan-Pelletier, Valerie M. (Zootaxa, 2017)
The oribatid mite family Tegoribatidae has been represented in continental North America by the genera Tegoribates and Tectoribates. Herein, I describe a new genus of Tegoribatidae from North America, Protectoribates, and two new species: Protectoribates occidentalis sp. nov., from forest habitats in western North American, and Tegoribates walteri sp. nov., from forest habitats in California, based on adults and immatures. The descriptions of adults of the type species of Tegoribates, T. subniger Ewing, and other North American species, T. americanus Hammer and T. bryophilus Woolley, are expanded and immatures of T. americanus are described for the first time. Immatures of Protectoribates are apheredermous whereas those of Tegoribates are eupheredermous, though retaining centrodorsal setae. Scutozetes Hammer 1952 is transferred from Tegoribatidae to Ceratozetidae after re-examination of type material. I provide a revised diagnosis for Tegoribates and a key to tegoribatid genera and species for North America. Finally, I provide a revised diagnosis for Tegoribatidae based on world genera.